High resolution additive manufacturing with acrylate based vitrimers using organic phosphates as transesterification catalyst. (14th April 2021) - Rossegger, Elisabeth; Höller, Rita; Reisinger, David; Fleisch, Mathias; Strasser, Jakob; Wieser, Viktoria; Griesser, Thomas; Schlögl, Sandra
Abstract: The present study highlights the high resolution additive manufacturing of covalent adaptable acrylate photopolymers, which undergo catalyzed transesterification reactions at elevated temperature. A methacrylate phosphate is introduced as a new transesterification catalyst, which considerably extends the toolbox of acrylate monomers for 3D printing of vitrimers, as it is easily soluble in a wide range of acrylate monomers and does not affect cure kinetics or storage stability of the resins. By appropriate design of monomer composition and catalyst, a series of acrylate-based vitrimers was prepared, whose glass transition temperature was conveniently adjusted by the chemical structure and functionality of the acrylate monomers. Rheometer studies revealed that the stress relaxation rate slows down with increasing crosslink density and lower amount of –OH moieties. In contrast, increasing the catalyst concentration in the photopolymer network from 5 to 15 wt% significantly accelerated the relaxation rate, with 63% of the initial stress being relaxed within 102 min. Complex 3D objects with feature sizes below 50 μm were manufactured by bottom-up digital light processing (DLP) and the dynamic nature of the covalent crosslinks endowed the printed structures with triple-shape memory and thermo-activated mendability. As shown by tensile tests, up to 99% of the initial strength could be recovered after the first healing step, showing the potential to improve functionality and lifetime of additively manufactured duromer networks. Moreover, the fast response time (60 s) of the shape recovery and the high resolution of the 3D printed structures pave the way towards a customized fabrication and miniaturization of soft robotic applications. Graphical abstract: Image 1 Highlights: Digital light processing 3D printing with acrylate based vitrimers is demonstrated. An organic phosphate is introduced as a new transesterification catalyst. Vitrimer networks with varying glass transition temperature are prepared. Complex 3D objects with feature sizes below 50 μm are manufactured. Structures feature triple-shape memory and thermo-activated mendability.